Carbon doped PDMS: conductance stability over time and implications for additive manufacturing of stretchable electronics. (8th February 2017) - Tavakoli, Mahmoud; Rocha, Rui; Osorio, Luis; Almeida, Miguel; de Almeida, Anibal; Ramachandran, Vivek; Tabatabai, Arya; Lu, Tong; Majidi, Carmel
Abstract: Carbon doped PDMS (cPDMS), has been used as a conductive polymer for stretchable electronics. Compared to liquid metals, cPDMS is low cost and is easier to process or to print with an additive manufacturing process. However, changes on the conductance of the carbon based conductive PDMS (cPDMS) were observed over time, in particular after integration of cPDMS and the insulating polymer. In this article we investigate the process parameters that lead to improved stability over conductance of the cPDMS over time. Slight modifications to the fabrication process parameters were conducted and changes on the conductance of the samples for each method were monitored. Results suggested that change of the conductance happens mostly after integration of a pre-polymer over a cured cPDMS, and not after integration of the cPDMS over a cured insulating polymer. We show that such changes can be eliminated by adjusting the integration priority between the conductive and insulating polymers, by selecting the right curing temperature, changing the concentration of the carbon particles and the thickness of the conductive traces, and when possible by changing the insulating polymer material. In this way, we obtained important conclusions regarding the effect of these parameters on the change of the conductance over time, that should be considered for additive manufacturing of soft electronics. Also, we show that these changes can be possibly due to the diffusion from PDMS into cPDMS.